Prediction of Initial Void Ratio from the Natural Moisture Content of Cohesive Soils - Ndubuisi O. OBAJI; Oladayo O. KOMOLAFE; Joy A. OKE, (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
Initial void ratio is an important compressibility parameter needed for the calculation and estimation of consolidation settlement of structural foundations, prediction of pre-consolidation pressure, and the determination of compression in cohesive soils. This initial void ratio is usually determined by a time-consuming process of conducting one-dimensional consolidation tests in the laboratory from undisturbed soil samples recovered from exploratory boreholes. However, not much attention has been given to the prediction of this important consolidation parameter especially for use in situations where undisturbed samples are not available. To address this limitation, one-dimensional consolidation tests were conducted on 319 undisturbed cohesive soil samples which were obtained from exploratory soil boreholes drilled at 29 sites within Lagos and its environs in Nigeria to predict the initial void ratio from their natural moisture contents. The initial void ratio of each sample was determined using the data obtained from consolidation test results and correlation analysis was made with their respective natural moisture content; an index property of the soil. The results showed that the initial void ratio has a strong correlation with the natural moisture content which is a basic soil parameter that is easily determined in the laboratory using disturbed samples. A linear equation was then developed for the estimation of this initial void ratio. This developed equation is practically useful where undisturbed soil samples are not available for laboratory consolidation analysis and so, disturbed soil samples are used to determine the natural moisture content which will then be a useful parameter for the initial void ratio prediction.